Challenging the colonial legacy of/at Macquarie. (4th August 2021) - Howitt, Richard; Holt, Leanne; Locke, Michelle Lea
Abstract: Macquarie University takes its name from a man known simultaneously as the founding father of Australia, its greatest colonial administrator, a key inspiration for Australia's egalitarian ethos, the military strategist who authorised the Appin Massacre, and committed civiliser of the uncivilised native peoples of Sydney who established the first institutions aimed at educating Aboriginal children by separating from their families, culture, and language. This article explores Macquarie's ambiguous legacy and considers how it is mobilised to promote the university. It discusses how the university community might engage with the "Macquarie legacy" and take responsibility for its implications for Macquarie University. Decolonising this particular university must involve much more than simple renaming—although even that would be far from simple. Transformation of the institution into a partner with Dharug and other Indigenous groups must involve uncomfortable and ultimately transformational reflection and action on the purposes, processes, and outcomes of education, on the nature and purposes of partnership, and more generally on the nature of decolonising transformations. Abstract : Decolonising Macquarie University is not simply a matter of renaming to displace a colonial figure or replacing his name with an Indigenous term. It demands rethinking how to take responsibility for carrying such a name, and reshaping the university's contemporary and future practices in teaching, research and relationships with the Dharug custodians of the campus.